Penggunaan Sikat Gigi Berbahan Elastomer Untuk Meningkatkan Keterampilan Menyikat Gigi dan Menurunkan Debris Anak Tunadaksa - Agno Elman Efzi; Tri Wiyatini; Bedjo Santoso; Rifka Annisa; Gusti Aprilisa Nurhuda (ABDIGI : JURNAL PENGABDIAN MASYARAKAT KESEHATAN GIGI, 2023)
Children with special needs (ABK) are children with limited development of physical and mental conditions characterized by behavior or emotions. In this case, a child with disabilities is a child who has abnormalities or defects in the muscular, bone, joint and nervous systems caused by diseases, viruses, accidents both before birth, at birth and after birth. Limitations that become obstacles in brushing teeth in a good and correct way cause high dental and oral health problems in children with disabilities. This study aims to determine the effectiveness of using elastomeric toothbrushes to improve brushing skills and reduce debris index rates in children with disabilities. The assessment of this program uses a health system approach, namely: Input – Process – Output. The results of toothbrushing skills in children with disabilities were found significant changes between the results before and after the intervention with statistical tests paired sample t-test and Wilcoxon with p-values of 0.001 and 0.017 (<0.05) respectively, which means that the use of toothbrushes made from elastomers is effective for improving brushing skills and reducing debris index in children with disabilities. The problem solving program for children with disabilities in SLBN Jepara is to implement innovative toothbrush models with elastomer materials for children with disabilities and conduct training on how to brush teeth properly and correctly for children with disabilities